2020
DOI: 10.3390/ijerph17249548
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Breadcrumbing in Affective-Sexual Relationships (BREAD-ASR) Questionnaire: Introducing a New Online Dating Perpetration

Abstract: New technologies are changing people’s lifestyles and in turn, their way of relating to and interacting with others. Breadcrumbing is one of the new 2.0 concepts linked to the virtual relationship paradigm. This study aimed to design and psychometrically test the Breadcrumbing in Affective-Sexual Relationships (BREAD-ASR) Questionnaire to explore breadcrumbing perpetration in adolescent relationships online. A total of 247 adolescents participated in a paper-and-pencil survey carried out from March to June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Several studies (LeFebvre et al, 2019; Navarro et al, 2020; Rodríguez-García et al, 2020) have noted an additional, ghosting-like phenomenon that often manifests in the dissolution of romantic relationships. “Breadcrumbing” is the act, preceding that of ghosting per se, of leading someone on through superficial acts of interest, only to hurt the other through empty promises and ultimately, abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (LeFebvre et al, 2019; Navarro et al, 2020; Rodríguez-García et al, 2020) have noted an additional, ghosting-like phenomenon that often manifests in the dissolution of romantic relationships. “Breadcrumbing” is the act, preceding that of ghosting per se, of leading someone on through superficial acts of interest, only to hurt the other through empty promises and ultimately, abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…(BREAD-ASR; [ 16 ] is a 16-item measure that assesses breadcrumbing engagement behaviours. Item examples: “I avoid being in person with my partner”; “I contact my partner when I feel alone”; “Communication with my partner depends on my interest and availability”.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is still little empirical evidence regarding the breadcrumbing phenomenon, the available research has shown that experiencing breadcrumbing is associated with feelings of helplessness and self-doubt, lower self-esteem, experience of loneliness, and is also related with lower life satisfaction and difficulties in the development of future relationships [ 14 , 15 ]. Breadcrumbing has been also associated with problems on self-concept, self-confidence and emotional stability on those who engage in it [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations